The Violation of Politeness Maxims in Ridwan Kamil's Old Tweet about Jakarta - Sartika Putri Sailuddin; Fitriningsih Pratiwi Mahmud; Nur Fajrhi (Tekstual, 2025)
Politeness is one of the basics in creating effective communication in public spaces. One of the public spaces that is quite often used when communicating is social media, one of which is Twitter. People, including politicians, often express their opinions on certain issues through Twitter. Ridwan Kamil expressed his opinion about the characteristics of Jakarta residents long before entering politics. The tweet received many negative responses from netizens because it was considered impolite. This study aims to analyze the pragmatic features of the tweet by identifying violations of the principle of politeness and discussing its effectiveness on political discourse and digital communication. The data used are Ridwan Kamil's tweets in 2011, which mention in detail the characteristics of Jakarta residents, which were reposted by the @txtdrjkt account. Data analysis uses a discourse analysis approach guided by the theory presented by Leech (1991). The results of the analysis show that through a single tweet, Ridwan Kamil also violates the maxims of tact, generosity, approbation, modesty, agreement, and sympathy.